Relationship between the diversity and mowing in cleared grassland areas in the Börzsöny mountains - Fehér, Zsófia (Gyepgazdálkodási Közlemények, 2020)
Nowadays, mowing has an increasing role in the management of semi-natural and nature conservation areas. Semi-dry grasslands have been formed on cleared areas of forest in the Pannon mountains, which would be reclaimed by forest without use of the areas by humans. In our work we analysed cleared grasslands. The questions we aimed to answer were the following:(i) What kind of vegetation changes were caused by different land use types?(ii) Is mowing a proper method for grassland management and nature protection in the studied system?(iii) Do the species composition and the diversity vary within two years when conditions of precipitation are different?In four sampling areas situted in Börzsöny mountains (North-Hungary), we registered the plant species and their cover values in ten quadrats per sampling area. We performed a site assessment in April, June and October, 2013-2014. We analysed the data by using cluster and ordination processes and we compared the sampling areas on the basis of the humidity preference and Shannon’s index of diversity. From nature conservation’s point of view, it is favourable that the cover of Potentilla alba occurring in the area was high. It is a specialist plant species with low stress resistance. However, due to tourism, it occured less frequently in the area and Bromus erectus became dominant instead. The species whose cover was more extensive in areas not affected by tourism – for example Alopecurus pratensis, Galium verum, Carex praecox, Trisetum flavescens – occurred less frequently in areas affected by tourism. On the short run, species did not completely disappear due to the changing conditions but their abundance decreased, as has been already supported by other surveys. The ordination analysis showed that the composition of species considerably differed with the portions of land cultivated in different ways. The change of the cover values was apparent not only in the case of the dominant species but of also in case of species with smaller cover. The decrease of diversity, the change of plant cover, the decrease of number of sensitive species as a result of tourism are typical phenomena all over the world. The Shannon’s diversity records showed that due to human presence and trampling the diversity declined. It was considerably lower in the year with less rain. In the year with more rain the diversity of species was considerably higher, however, the difference in between the surveyed areas was large. All these examples draw attention to the important role of environmental factors alongside the human factors. The water reserve also influences the productivity of grasslands and water has primary importance in the structure of plant communities. According to the survey, in the two areas not affected by tourism, in the rainier year the difference between the humidity preference of the species of the dry and the less dry patches became similar. On these areas, there were more species with higher humidity preferences in the rainier year, however, this tendency could not be observed in the rainier year on areas affected by tourism. The areas affected by tourism may react in a less flexible manner to the change in precipitation conditions. Based on our analysis, we can conclude that the surveyed semi-dry grasslands are extremely rich in species and therefore proper grassland management plans are needed. To preserve grasslands of high natural value, the impacts of the environmental factors should also be considered in addition to becoming acquainted with the history and the present conditions of landscape use.